'Continuous Improvement' and the Team Model at Honda of Canada Manufacturing - Nurcombe, Sid (My University, 2007)
This study examines how workers experience Japanese inspired manufacturing practices at Honda of Canada Manufacturing (HCM), Alliston assembly operations and associated parts suppliers. To address how lean production methods are changing production workers responsibilities and impacting job satisfaction, the nature of production work, and the implementation of the Kaizen philosophy are investigated. I predicted that production work at HCM and its suppliers consists of some of the same alienating working conditions as experienced by workers in traditional operations with less job rotation or formal employee participation schemes. The data revealed that despite job rotation production work at these operations is alienating: workers reported that their jobs were "mind-numbing" and that they were simply there for the pay-cheque. Interestingly, some of the same individuals also reported job satisfaction when their Kaizen suggestions were implemented-but most participants noted the difficulty in actually getting their suggestions to be acted on, and the arbitrary way in which managers can administer the participation programs. Secondly, it was predicted that lean production model would result in more alienating relationships between co-workers. The relations constructed through teamwork and total quality management, can combine to create situations where employees are encouraged to point out the inferior performance of their co-workers. Data demonstrating this hypothesis is more suggestive and less conclusive. While finding the answer to this question, two other issues that warrant attention were observed. Initially, production work at HCM is stratified into an informal hierarchy of jobs, beginning with assembly work and ending with final vehicle inspection. Intertwined with the stratification of jobs is a segmented internal labour market in which 'contract' and temporary help agency employees provide a just-in-time workforce. A secondary conclusion is made that suggests the team model results in more alienating relationships between co-workers when there is a two-tier employment system.
Keywords: Social Work; Work, Economy and Organizations; Social Work